Las asignaciones presupuestarias y su incidencia en el cumplimiento de las competencias municipales del GAD Chone periodo fiscal 2020 - Endara Zambrano, Darwin Rider (2022)
The purpose of this research is to analyze the allocations of the General State Budget and its impact on the fulfillment of municipal competencies, in order to optimize the sources of financing of the Autonomous Municipal Government of the Chone canton in the fiscal period 2020. Therefore, the types of research used were field, bibliographic and descriptive, in turn, deductive, inductive and analytical research methods were applied; subsequently, as a technique for collecting information, an interview was applied to the directors in charge of the different areas of the GADM of the canton Chone. Among the main results obtained, it is highlighted that the estimated income budget in 2020 corresponded to $48.809.075,47, while the executed income budget was $20.307.406,57; likewise, in this year an expenditure budget of $48.809.075,47 was estimated and an executed expenditure budget of $19.931.740,45 was obtained. In addition, among the main reforms carried out are related to the credit supplement, budgetary liquidation of income and expenses, fiscal year transfer, decrease reform, transfer and emergency reforms. It is worth mentioning that in 2020 the Control and Security Directorate presented the lowest budget execution index, since it had a percentage value of 15.43%, while the highest index for this period was 69.65%, which was obtained by the Public Works Directorate. Therefore, it is concluded that the improvement plan is focused on the budget execution of the GADM of the canton of Chone and the achievement of institutional objectives.